OPTIMIZATION OF CONSERVATIVE TREATMENT OF REVIVING UTERINE BLEEDING OF PUBERTY (World Bulletin of Public Health, 2024)
This article focuses on optimizing conservative therapy for menstrual bleeding in adolescent girls, with an emphasis on recurrent cases
Keywords: Uterine bleeding of puberty; recurrent bleeding